Fabrication of high-quality electrode films for solid oxide fuel cell by screen printing: A review on important processing parameters - Baharuddin, Nurul Akidah; Abdul Rahman, Nurul Farhana; Abd. Rahman, Hamimah; Somalu, Mahendra Rao; Azmi, Mohd Azham; Raharjo, Jarot (Wiley, 2020)
Summary Solid oxide fuel cell (SOFC) is known as the most efficient fuel cell, with an efficiency of 60% in converting fuel to electricity and up to 80% in fuel to energy conversion (including heat). A SOFC consists of three primary components, namely, anode, electrolyte and cathode. Given the demand for reducing the operating temperature below 800 C, not only thin electrolytes have become a necessity for their ability to reduce ohmic losses but also high-quality porous electrode (anode and cathode) films for their ability to accelerate electrochemical reactions with fuels. In this context, screen printing is known for its capability to form high-quality porous electrode films in a cost-effective manner. In addition, screen printing offers fabrication-related parameters that can be easily manipulated to produce different film qualities depending on the requirements which have been explored in various applications. However, screen printing is only utilised in SOFC application as a fabrication tool to produce electrode films, neglecting the effects of its fabrication-related parameters on electrode performance, as indicated by the limited number of related works. Despite limited resources, this study aims to review the fabrication-related parameters in producing SOFC electrodes through screen printing and their effects on electrochemical performance. The parameters at different stages (ie, prior, during and post printing), including ink formation, printing numbers and sintering, are extensively reviewed. To the best of our knowledge, this study is not only the first review that discusses the effects of screen-printing fabrication-related parameters on electrode potentials but also offers suggestions on future directions regarding these parameters towards the improvement of SOFC performance. Novelty Statement Among all thin-film fabrication methods, screen printing is known for its capability to form homogenous-porous SOFC electrode films; however, the processing parameters of screen printing at three primary stages (prior, during, and postprinting) are rarely explored. As such, the current paper highlights important parameters in screen printing, such as ink rheology, printing number, and sintering, to contribute to the understanding of the influence of these parameters on SOFC electrode film quality and their effects on electrochemical performance.